Immunomodulatory effects of nisin in turbot (Scophthalmus maximus L.) - Villamil, L.; Figueras Huerta, Antonio; Novoa, Beatriz (Fish & Shellfish Immunology, 2003)
13 páginas, 4 figuras In the present work, the e#ect of nisin on the non-specific immune response of turbot (Scophthalmus maximus L.) leukocytes has been studied both in vitro and in vivo. The head kidney macrophage chemiluminescent (CL) response was significantly increased with intermediate doses of nisin (2·5 and 0·025 g ml 1) whilst the higher dose (25 g ml 1) significantly decreased the response after 24 h incubation. When the incubation time was extended to 72 h, significant di#erences between doses were observed and the lower nisin concentration (0·025 g ml 1) appeared to be the optimum dose for increasing the CL response. The phagocytic activity of HK macrophages was also a#ected by in vitro nisin treatments. Nisin at 0·25 g ml 1 and 0·025 g ml 1 significantly stimulated the response after 24 and 72 h incubation respectively. Nitric oxide (NO) production by HK macrophages was not influenced by any nisin concentration employed for 24 or 72 h incubations In vivo, one week post injection, a slightly but non-significant stimulation of the CL response was observed with the lowest nisin concentration (0·0025 g fish 1). NO in serum and serum antibacterial index were not significantly a#ected by nisin treatments. On the other hand, lysozyme concentration in serum was significantly augmented with the lowest nisin dose (0·0025 g fish 1). The antibacterial e#ect of nisin against the fish pathogenic bacteria Carnobacterium piscicola (CECT 4020) was also demonstrated in vitro. This work was partially supported by the project 1FD97-0044-C03-03 from FEDER funds and a grant from Caixa Galicia (Spain). Peer reviewed